2018
DOI: 10.2175/106143017x15131012153167
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic‐Aerobic Combined System for the Biological Treatment of Azo Dye Solution using Residual Yeast

Abstract: This study aimed to investigate the treatment efficiency of a synthetic dye solution in an anaerobic-aerobic combined reactor system, using pretreated residual yeast as a nutrient source and redox mediator. The applicability of the residual yeast as a nutrient source was firstly evaluated in anaerobic batch tests. Subsequently, two continuous bench-scale treatment settings were studied: (1) an Upflow Anaerobic Sludge Blanket (UASB) reactor followed by an activated sludge system and, (2) a UASB reactor followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Previous studies also showed that the residual yeast could be used as the unique source of carbon and redox mediators in the anaerobic treatment of azo dyes. In those studies, the authors verified that the discoloration rates of dye solutions were practically the same (~72%) when using standard nutrient solution containing yeast extract and when using only residual yeast [11,12]. Moreover, color removal rates as high as 94% was observed for 10-fold diluted textile effluent supplied with commercial yeast extract in bench scale UASB [2].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Previous studies also showed that the residual yeast could be used as the unique source of carbon and redox mediators in the anaerobic treatment of azo dyes. In those studies, the authors verified that the discoloration rates of dye solutions were practically the same (~72%) when using standard nutrient solution containing yeast extract and when using only residual yeast [11,12]. Moreover, color removal rates as high as 94% was observed for 10-fold diluted textile effluent supplied with commercial yeast extract in bench scale UASB [2].…”
Section: Discussionmentioning
confidence: 75%
“…Residual yeast biomass belonging to Saccharomyces cerevisiae species was obtained from a small brewery pretreated through osmotic lysis [11,12]. For this, yeasts were taken directly from fermentation vats and submitted to a clarification process, which consisted in a sequence of centrifugations and addition of ethanol solution 96% (10% M/M).…”
Section: Residual Yeastmentioning
confidence: 99%
See 2 more Smart Citations
“…It accumulates in large amounts in the ecological environment, which will seriously affect photosynthesis in the aquatic environment and may cause cancer and mutagenesis [7]. At present, treatment methods mainly include oxidation method [8], biological method [9], and adsorption method, among which adsorption method is a fast, inexpensive, and universal treatment method [10].…”
Section: Introductionmentioning
confidence: 99%